Anthropometric and Physiological Predictors of Soccer Skills in Youth Soccer Players - Chanawat Sanpasitt; Atcharat Yongtawee; Thitiwat Noikhammueang; Daranee Likhitworasak; Minjung Woo (OVS LLC, 2023)
Study purpose. This study aimed at investigating the anthropometric and physiological characteristics that affect soccer skills in advanced-level youth soccer players. Materials and methods. Ninety advanced youth male soccer players from the U-18 division 1 soccer club were enrolled to participate in this study. The participants were classified into three different positions: defenders, midfielders, and forwards. The anthropometric profiles (height, weight, and body fat) and physiological variables (Y-balance test, Yo-Yo Intermittent Recovery Test Level 1, running-based anaerobic sprint test, sit-up test, countermovement jump test, drop jump test, arrowhead agility test, and 40-m sprint test) were assessed. Soccer-specific skills were measured using the Loughborough soccer passing and shooting protocol. Results. The multiple regression analysis revealed a statistically significant relationship between physical factors and the Loughborough soccer passing ability (R2 = 0.291, F(15, 74) = 2.200, p = 0.015). The results indicated that the relative maximum power displayed the strongest association with passing ability, followed by sit-up, countermovement jump without and with arm swing, and fatigue index. Concerning the shooting performance, the predictors accounted for 21.8% of the variance, with sit-up being the sole significant predictor among other factors. Conclusions. Our findings underscore the significance of relative maximum power, fatigue tolerance, muscular power, and core strength as valuable predictors for enhancing passing ability. In addition, abdominal strength emerged as a crucial indicator of shooting performance. Soccer coaches could use the essential information described in this study for talent identification purposes.